1998
DOI: 10.1063/1.121149
|View full text |Cite
|
Sign up to set email alerts
|

A low pressure mercury vapor resonance ionization image detector

Abstract: Narrow-band spectrally selective image detection based upon the resonance ionization of mercury atoms in a low pressure cell is described. Image dimensions and intensities were measured versus the wavelength of ionizing laser radiation and the dependence upon the voltage applied to electrodes was studied. The position sensitive image of the electron beam, created by two-step resonance photoionization of mercury, was studied when the detected laser beam was scanned spatially. A distorting influence of space cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The configuration and detailed principle of operation of the RIID are described elsewhere. [1][2][3][4] Briefly, the detector, consisting of a partially metal coated input window and a microchannel plate coupled with a P20 phosphor screen, was assembled in a six-way cross-vacuum chamber. The chamber was evacuated to a pressure of ϳ1 torr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration and detailed principle of operation of the RIID are described elsewhere. [1][2][3][4] Briefly, the detector, consisting of a partially metal coated input window and a microchannel plate coupled with a P20 phosphor screen, was assembled in a six-way cross-vacuum chamber. The chamber was evacuated to a pressure of ϳ1 torr.…”
Section: Methodsmentioning
confidence: 99%
“…The figure of merit of these detectors as well as their potential applications have been extensively discussed. 1 An RIID based on Hg vapor was first described by Matveev et al 2 and subsequently optimized by Pappas et al 3 Recently, another RIID using Cs as an active element was successfully demonstrated and its operational characteristics were evaluated. 4 The present note, as a continuation of the RIID development, describes a detector with two active elements (Cs and Hg), which exhibits dual-wavelength detection capability.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques have been used to detect adsorbed species using optical or conductometric sensors, quartz crystal microbalance and cantilever [1][2][3][4][5][6][7][8]. The advent of nanostructured materials has created many opportunities to dramatically enhance the ability to detect adsorbed chemicals.…”
Section: Introductionmentioning
confidence: 99%